We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
554
1
avatar

ƒ(−1) if ƒ(x) = 3(x −1)² + 5?

 Jul 8, 2015

Best Answer 

 #1
avatar+105411 
+8

ƒ(−1) if ƒ(x) = 3(x −1)² + 5?     we're just substituting "-1" into this for "x" and evaluating...so we have....

 

3 (-1-1)2 + 5  =

 

3(-2)2 + 5  =

 

3(4) + 5 =

 

12 + 5  =

 

17

 

 

  

 Jul 8, 2015
 #1
avatar+105411 
+8
Best Answer

ƒ(−1) if ƒ(x) = 3(x −1)² + 5?     we're just substituting "-1" into this for "x" and evaluating...so we have....

 

3 (-1-1)2 + 5  =

 

3(-2)2 + 5  =

 

3(4) + 5 =

 

12 + 5  =

 

17

 

 

  

CPhill Jul 8, 2015

11 Online Users